2020
DOI: 10.1101/2020.10.02.324145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infected cells present HLA-I peptides from canonical and out-of-frame ORFs

Abstract: T cell-mediated immunity may play a critical role in controlling and establishing protective immunity against SARS-CoV-2 infection; yet the repertoire of viral epitopes responsible for T cell response activation remains mostly unknown. Identification of viral peptides presented on class I human leukocyte antigen (HLA-I) can reveal epitopes for recognition by cytotoxic T cells and potential incorporation into vaccines. Here, we report the first HLA-I immunopeptidome of SARS-CoV-2 in two human cell lines at diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 63 publications
1
29
0
Order By: Relevance
“…As SARS-CoV-2 shows high genomic similarity to the SARS-CoV-1 virus 1 , we elected to analyze both SARS-CoV-1/2 mRNA sequences and extract CAMAP scores for all their potential MAPs. We first confirm that naturally processed SARS-CoV-1 specific MAPs (identified since the pandemic of 2002-2004), and mass spectrometry identified SARS-CoV-2 MAPs 23 are indeed associated with high CAMAP scores. We then used both CAMAP scores and predicted MHC-I binding affinity to define a set of 15 very common HLA class I alleles in order to identify a combination of 48 high potential SARS-CoV-2-specific MAPs.…”
Section: Anothersupporting
confidence: 58%
See 2 more Smart Citations
“…As SARS-CoV-2 shows high genomic similarity to the SARS-CoV-1 virus 1 , we elected to analyze both SARS-CoV-1/2 mRNA sequences and extract CAMAP scores for all their potential MAPs. We first confirm that naturally processed SARS-CoV-1 specific MAPs (identified since the pandemic of 2002-2004), and mass spectrometry identified SARS-CoV-2 MAPs 23 are indeed associated with high CAMAP scores. We then used both CAMAP scores and predicted MHC-I binding affinity to define a set of 15 very common HLA class I alleles in order to identify a combination of 48 high potential SARS-CoV-2-specific MAPs.…”
Section: Anothersupporting
confidence: 58%
“…In a recent study, Daouda We also showed that mass-spectrometry identified SARS-CoV-2 MAPs were also associated with higher CAMAP scores. Of note, in Weingarten-Gabbay et al study, the 2 proteins that gave rise to the highest number of MAPs were ORF1ab (11/30, 37%) and the S proteins (7/30, 23%), while only 1 peptide originated from each of the M and N proteins 23 . This result is very surprising, as the mRNA expression levels of the ORF1a and ORF1ab is 10 to 1000-fold lower than that of structural ORFs 30 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…St-Germain et al [36] proteomics yes yes no Stukalov et al [116] proteomics no no no Sun et al [117] glycoproteomics no no NA Supekar et al [118] glycoproteomics yes partial NA Watanabe et al [133] glycoproteomics no no NA Weingarten-Gabbay et al [134] proteomics no no no Wendt et al [135] proteomics no no no Yang, Du, and Kaltashov [141] proteomics no no NA Zecha et al [142] proteomics yes partial no Zhao et al [144] glycoproteomics yes partial no…”
Section: Referencementioning
confidence: 99%
“…For the bulk RNA-sequencing (RNA-seq) datasets whose read count data is available at the time of analysis, we performed differential expression (DE) analysis comparing the SARS-CoV-2-infected or positive samples to the non-infected control or negative samples with DESeq2 ( Love et al 2014 ). For Weingarten-Gabby et al 2020 , a nested design for DE was needed and DESeq2 failed to run properly, and limma-voom ( Law et al 2014 ) was used. For Butler et al 2020 and Xiong et al 2020 , we obtained the DE results provided from the supplementary materials of the respective publication, as we were not able to obtain their gene-level expression data at the time of analysis.…”
Section: Methodsmentioning
confidence: 99%